New Biology Identified by PGx Is Foundation for New Strategies in BC - Mosley, Mary (MD Conference Express, 2014)
The results of genome-wide association studies and functional genomics studies reviewed in this article have elucidated new biology in breast cancer that provides a foundation for further laboratory and clinical research to identify genetic variability and its effects on breast cancer prevention and treatment.